Student perception of role of sport at university - Nešić Milan; Nešić Branimir (College of Sports and Health, Belgrade, 2020)
The concept of university sports in Serbia is still dominantly based on occasional sports manifestations (competitions) for students. Mostly in the shape of single ad-hoc tournaments in different areas of sport or as competitions of student athletes within the University sports association. The current position of a majority of student population in terms of university sports in Serbia can be characterized as passive (spectators), while direct participants, who are recruited from the field of active competitive sports, have this only as an "additional" obligation within the sport they already practice in "their" sport clubs. Therefore, students' perception of the role of sports/physical activity at university represents a very important determinant for creating adequate (new) program contents, concepts and for the implementation of physical education in higher education institutions in Serbia. The goal of this research, which is realised as an empirical non-experimental study, is to identify the attitude and opinion of students about the role of sport and organized physical exercising at university. The sample involved 227 students at the University of Novi Sad and Educons University from Sremska Kamenica. Survey was used as the basic research technique, and the instrument was constructed as a questionnaire whose basic semantic structure was based on similar instruments used in a few earlier studies. The results showed that the currently trend indicates a drop in regular practice of sport after enrolment in faculty, but youth positively perceive the role of sports at higher education institutions, clearly recognizing its importance in social interaction. Therefore, pedagogical implications of this research can certainly dominantly relate to management structures of higher education institutions in shape of a clear message about the necessity to introduce more intense education of all education stakeholders about the values and importance of physical activity (physical exercising) of youth. In that context, they also encourage changes in overall education policy in Serbia.